The Internet of Things Security Challenges: Survey - Beggar, Inès; Riahla, Mohamed Amine (University of Eloued جامعة الوادي, 2022)
The Internet of Things (IoT) and its security issues are gaining interest in recent years. It is more than necessary to take charge of them as soon as possible and to find specific solutions to the IoT. These allow it to wait for its full maturity and to take advantage of the simplicities it brings to our daily life. But to do so, it is necessary to identify and the master ins and outs of the problem which is developed in the present work. However, this paper aims on the one hand to present the Internet of Things in point form, and on the other hand to address the security of the same points as the presentation of the IoT. Moreover, the properties of the IoT are discussed and compared to traditional networks, also the level of security required according to the area of application and security from a point of view; actors of the IoT ecosystem. Besides, the existing architectures are examined in order to allow future research to selfpositioning and better understand the security issue.
Forum Intervention of Artificial Intelligence and Its Applications. Faculty of Exat science. University of Eloued
Keywords: Internet of Things, Security, Actors of IoT ecosystem.